A Survey on VANET Security Attacks and Cryptographic Solutions: Exploring Security Measures in Vehicular Ad-Hoc Networks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Vehicular ad-hoc network (VANET) is being broadly used and considered important among the emerging technologies that guarantee broad range of applications in the field of military, medical, home and environment. Upcoming research in the area of Vehicular ad-hoc network technology has introduced a new part in the world of wireless communication. For communication, VANETs use inter-communication technologies such as GPS, digital maps, digital short range communication, in-built communication system to reduce traffic congestion and accidents on roads. VANET can be used for communication purpose where vehicles can exchange the information with other vehicles and roadside units. The data can be emergency messages or some entertainment related messages. Safety becomes one of the most important issues in VANET. To ensure security, cryptographic solutions are used.